(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper a specific end goal to design a RC structural element, it is vital to know behavior of reinforced concrete structures and a comprehension of the fundamental material properties. It is likewise vital to get to know the fundamental ideas identifying with execution criteria in reinforced concrete design. The point of structural design is to design a structure with the goal that it satisfies three criteria in particular wellbeing, satisfactory functionality and economy. Wellbeing incorporates quality, concreteness and basic honesty. Sufficient workableness incorporates concreteness, strength, and creep. The conduct of segment at different phases of stacking can be examined in two sections i.e. starting un-split stage and a definitive condition at collapse.